2021
DOI: 10.1111/ele.13886
|View full text |Cite
|
Sign up to set email alerts
|

Keep your friends close: Host compartmentalisation of microbial communities facilitates decoupling from effects of habitat fragmentation

Abstract: Root‐associated fungal communities modify the climatic niches and even the competitive ability of their hosts, yet how the different components of the root microbiome are modified by habitat loss remains a key knowledge gap. Using principles of landscape ecology, we tested how free‐living versus host‐associated microbes differ in their response to landscape heterogeneity. Further, we explore how compartmentalisation of microbes into specialised root structures filters for key fungal symbionts. Our study demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…It was shown that geographic distance had a small effect on AMF communities, because a single plant species in agricultural land may homogenize the AMF communities over a certain distance [ 41 ]. Furthermore, the host compartmentalization of microbial communities facilitates the decoupling from effects of habitat fragmentation [ 42 ]. In our study, P. phaseoloides plays an important role in shaping AMF communities, thereby overriding geographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that geographic distance had a small effect on AMF communities, because a single plant species in agricultural land may homogenize the AMF communities over a certain distance [ 41 ]. Furthermore, the host compartmentalization of microbial communities facilitates the decoupling from effects of habitat fragmentation [ 42 ]. In our study, P. phaseoloides plays an important role in shaping AMF communities, thereby overriding geographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, this strategy may be inefficient if expansion and evolution of the symbionts in the population core facilitates the quick restoration of the population at the range edges. Our general framework may be adapted to host-symbiont populations expanding over a heterogeneous landscape, such as a fragmented or disturbed habitat (Willing et al, 2021), and to consider range overlaps with native populations (Dickie et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations of specific mechanisms driving foliar fungal sourcing in agricultural systems are warranted. For example, we did not identify fungi from native vegetation or directly consider natural vegetation characteristics beyond cover that might control fungal propagule supply, such as native host diversity, vertical structuring, edge effects, and fragmentation (Martin et al, 2019;Willing et al, 2021). Similarly, our survey of environmental, soil, and plant traits was not exhaustive, and other factors might be more relevant (Lee and Hawkes, 2021).…”
Section: Discussionmentioning
confidence: 99%